Invertebrates from the Low Head Member (Polonez Cove Formation, Oligocene) at Vaureal Peak, King George Island, West Antarctica - Quaglio, Fernanda; Anelli, Luiz E.; Santos, Paulo R. dos; Perinott, José Alexandre de Jesus [UNESP]; Rocha-Campos, Antonio C. (Cambridge University Press, 2008)
Eight taxa of marine invertebrates, including two new bivalve species, are described from the Low Head Member of the Polonez Cove Formation (latest early Oligocene) cropping out in the Vaureal Peak area, King George Island, West Antarctica. The fossil assemblage includes representatives of Brachiopoda (genera Neothyris sp. and Liothyrella sp.), Bivalvia (Adamussium auristriatum sp. nov., ?Adamussium cf. A. alanbeui Jonkers, and Limatula (Antarctolima) ferraziana sp. nov.), Bryozoa, Polychaeta (serpulid tubes) and Echinodermata. Specimens occur in debris flows deposits of the Low Head Member, as part of a fan delta setting in a high energy, shallow marine environment. Liothyrella sp., Adamussium auristriatum sp. nov. and Limatula ferraziana sp. nov. are among the oldest records for these genera in King George Island. In spite of their restrict number and diversification, bivalves and brachiopods from this study display an overall dispersal pattern that roughly fits in the clockwise circulation of marine currents around Antarctica accomplished in two steps. The first followed the opening of the Tasmanian Gateway at the Eocene/Oligocene boundary, along the eastern margin of Antarctica, and the second took place in post-Palaeogene time, following the Drake Passage opening between Antarctic Peninsula and South America, along the western margin of Antarctica.
Keywords: bivalves; brachiopods; Bryozoa; Echinoidea; Palaeogene; Pectinidae; Polychaeta; taxonomy